Itolizumab in combination with methotrexate modulates active rheumatoid arthritis: safety and efficacy from a phase 2, randomized, open-label, parallel-group, dose-ranging study. Issue 4 (April 2016) - Chopra, Arvind; Chandrashekara, S.; Iyer, Rajgopalan; Rajasekhar, Liza; Shetty, Naresh; Veeravalli, Sarathchandra; Ghosh, Alakendu; Merchant, Mrugank; Oak, Jyotsna; Londhey, Vikram; Barve, Abhijit; Ramakrishnan, M.; et al.
Abstract The objective of this study was to assess the safety and efficacy of itolizumab with methotrexate in active rheumatoid arthritis (RA) patients who had inadequate response to methotrexate. In this open-label, phase 2 study, 70 patients fulfilling American College of Rheumatology (ACR) criteria and negative for latent tuberculosis were randomized to four arms: 0.2, 0.4, or 0.8 mg/kg itolizumab weekly combined with oral methotrexate, and methotrexate alone (2:2:2:1). Patients were treated for 12 weeks, followed by 12 weeks of methotrexate alone during follow-up. Twelve weeks of itolizumab therapy was well tolerated. Forty-four patients reported adverse events (AEs); except for six severe AEs, all others were mild or moderate. Infusion-related reactions mainly occurred after the first infusion, and none were reported after the 11th infusion. No serum anti-itolizumab antibodies were detected. In the full analysis set, all itolizumab doses showed evidence of efficacy. At 12 weeks, 50 % of the patients achieved ACR20, and 58.3 % moderate or good 28-joint count Disease Activity Score (DAS-28) response; at week 24, these responses were seen in 22 and 31 patients. Significant improvements were seen in Short Form-36 Health Survey and Health Assessment Questionnaire Disability Index scores. Overall, itolizumab in combination with methotrexate was well tolerated and efficacious in RA for 12 weeks, with efficacy persisting for the entire 24-week evaluation period. (Clinical Trial Registry of India, http://ctri.nic.in/Clinicaltrials/login.php, CTRI/2008/091/000295).